Cost-Effectiveness of the Interventions for Severe Mental Illness (SMI) in Low and Middle-Income Countries (LAMICs): A Systematic Review - Abdul Latif; Martyn Lewis; Ghasem Yadegarfar; Zala Khan; Saeed Farooq (BJPsych Open, 2025)
Aims: Despite the high prevalence of mental illnesses, particularly Severe Mental Illness, there is limited literature on the cost-effectiveness of available interventions in low- and middle-income countries. Therefore this review aimed to assess the cost-effectiveness of the pharmacological and psychosocial interventions for Severe Mental Illness (SMI) in Low and Middle-Income Countries (LMICs).